Advances and Perspectives on the Epidemiology of Bovine Cryptosporidium in China in the Past 30 Years - Wang, Rongjun; Zhao, Guanghui; Gong, Yunya; Zhang, Longxian (Frontiers in Microbiology, 2017)
Major progress has been made in understanding the epidemiology of bovine Cryptosporidium in China in the past 30 years. The overall infection rate in that period was 14.50% (5265/36316), with different prevalence being observed among dairy cattle, yaks, beef cattle, and buffalo. The infection rate declined as the animals’ ages increased and the lowest prevalence occurred in winter. Ten Cryptosporidium species and two genotypes have been found in cattle, with C. parvum, C. andersoni, C. bovis, and C. ryanae being the commonest species. Cryptosporidium bovis rather than C. parvum predominated in preweaned dairy cattle, and C. parvum IIdA15G1 and IIdA19G1 were the only subtypes detected in dairy cattle. Two subtype families, IIa and IId, were found in yaks. Population genetic analysis detected an epidemic population structure in C. andersoni, which suggested that the prevalence of C. andersoni in China is not attributable to the introduction of dairy cattle. Moreover, C. parvum IId subtypes probably dispersed from western Asia to other geographic regions based on population genetic analysis of isolates from China, Sweden, and Egypt. Therefore, we hypothesize that Cryptosporidium was introduced into China in the past, and different populations formed progressively in various hosts in response to diverse factors, including the transmission dynamics, geographic isolation, host specificity, and large-scale farming. More epidemiological studies are required to test this hypothesis and to clarify the prevalence and transmission of Cryptosporidium species in China.